A DFT Study of Inter‐ and Intramolecular Aryne Ene Reactions. Issue 13 (17th March 2015) - Pérez, Patricia; Domingo, Luis R.
Abstract: The molecular mechanisms of inter‐ and intramolecular aryne‐ene reactions have been theoretically studied by DFT methods at the MPWB1K/6‐311G(d, p) level. These reactions proceed through a one‐step mechanism via nearly asynchronous transition states (TSs), in which the C–C single bond formation is slightly more advanced than the hydrogen transfer process. These ene reactions show very low activation enthalpies (<1 kcal/mol) and are strongly exothermic by more than 73 kcal/mol. An electron localisation function (ELF) topological analysis of the changes of electron density during these ene reactions indicates that the bonding changes are nonconcerted. ELF topological analysis of the electron density in the C1–C2 bonding region of benzyne indicates that the 1, 2‐pseudodiradical vinyl structure, rather than a structure with a C≡C triple bond, is responsible for the very high reactivity of these species. Abstract : Inter‐ and intramolecular aryne‐ene reactions occur through a one‐step mechanism via nearly asynchronous transition states, in which C–C bond formation is slightly more advanced than the hydrogen transfer process. Electron localisation function (ELF) topological analysis of the C1–C2 region of benzyne shows that the 1, 2‐pseudodiradical vinyl structure causes its high reactivity.